THE ROLE OF CUSTOMS IN CODIFICATION OF DIPLOMATIC AND CONSULAR LAW - Boghirnea, Iulia (International Journal of Legal and Social Order, 2024)
Diplomatic and consular customs are still a lively subject to research, being primary sources of diplomatic and consular law, important in maintaining peace and diplomatic relations between states. Therefore, using the methods of scientific legal research, we proposed, starting from the analysis of the process by which the old diplomatic customs were formed, the origin of diplomatic and consular customs but also the opinions formulated in the specialized literature, Romanian and foreign, relative to the new dynamics of the formation of new customs in the field of diplomatic and consular law with regard to the time factor, to identify their role in the codification of diplomatic and consular law as well as to point out the importance of recognizing and transposing customs into text in a certain political and diplomatic context between Yugoslavia and the Soviet Union, as a result of which there was this need to be codified in the two Vienna Conventions on Diplomatic Relations (1961) and Consular Relations (1963).